Foundations of engineering - Holtzapple, Mark Thomas; Reece, W. Dan (McGraw-Hill Higher Education, 2003)
This book gives freshman engineering students a solid foundation for all their future coursework. It provides an overview to the engineering profession, an introduction to the skills they will need to develop, as well as to fundamental engineering topics such as thermodynamics, rate processes, and Newton's laws. An important aspect of the book's approach is the method of Engineering Accounting, which casts the basic conservation laws (e.g., of energy or mass) as simple "accounting" procedures. This is a unifying concept that facilitates problem-solving across all engineering disciplines.